2003
DOI: 10.1097/01.tp.0000061612.78954.6c
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation for hepatopulmonary syndrome: A ten-year experience in Paris, France

Abstract: Our data strongly support the role of orthotopic liver transplantation in adult patients with HPS, regardless of its severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
119
1
9

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(136 citation statements)
references
References 26 publications
7
119
1
9
Order By: Relevance
“…In a retrospective review from 4 transplant centers (23 HPS patients) in Paris, France, Taille et al 6 showed that the mortality was 30.5% (7/23; six deaths within 6 months of OLT). 6 Perioperative mortality (2 deaths of multiorgan failure and refractory hypoxemia within 90 days of OLT) was 8.5%. Pre-OLT, 5 of 7 HPS patients had PaO 2 Ͻ 60 mm Hg.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a retrospective review from 4 transplant centers (23 HPS patients) in Paris, France, Taille et al 6 showed that the mortality was 30.5% (7/23; six deaths within 6 months of OLT). 6 Perioperative mortality (2 deaths of multiorgan failure and refractory hypoxemia within 90 days of OLT) was 8.5%. Pre-OLT, 5 of 7 HPS patients had PaO 2 Ͻ 60 mm Hg.…”
Section: Discussionmentioning
confidence: 99%
“…First, HPS has been shown to have an independent adverse effect on mortality before liver transplantation, 11 and second, complete resolution of HPS frequently occurs in patients surviving the transplant hospitalization. 1,5,6 If the patient survives the immediate postoperative course (intensive care unit/ transplant hospitalization), there is a high likelihood of normalization of arterial oxygenation over time (many months) with little chance of recurrence of HPS. 1,5,6,11,12 Several distinctions should be emphasized between our data and the survival analysis reported by Schenk et al 12 in 27 HPS patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If HPS develops, the risk of death in the next year is 41%. This syndrome can be considered as a separate indication for a liver transplant [13][14][15][16], but at the same time the severe hypoxia in the case of HPS is associated with a high risk of liver transplant complications (30% during the first 90 days) and increased gap between the transplant surgery and improvement in arterial oxygenation [17]. This complication is seen in 6-21% of the patients and carries a 45% chance of mortality [18].…”
Section: Prognosis and Treatment Optionsmentioning
confidence: 99%